2014
DOI: 10.1186/s13567-014-0076-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and detection of three new F17 fimbrial variants in Escherichia coli strains isolated from cattle

Abstract: F17 fimbriae are produced by pathogenic Escherichia coli involved in diarrhea and septicemia outbreaks in calves and lambs. These proteins result from the expression of four different clustered genes, namely f17A, f17D, f17C and f17G, encoding a pilin protein, a periplasmic protein, an anchor protein and an adhesin protein, respectively. Several variants of f17A and f17G genes have been reported and found genetically associated with typical virulence factors of bovine pathogenic E. coli strains. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
2
16
0
1
Order By: Relevance
“…These results were almost similar to other studies which demonstrated that the isolates of phylogroup A were prevalent in the intestinal tracts of most animals 24,37 and phylogroup B1 was dominant among isolates from healthy cattle. 38 In accordance with the previous reports in Iran, 23,39 this study showed that the phylogroup B1 was dominant in calves. The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations.…”
Section: Discussionsupporting
confidence: 81%
“…These results were almost similar to other studies which demonstrated that the isolates of phylogroup A were prevalent in the intestinal tracts of most animals 24,37 and phylogroup B1 was dominant among isolates from healthy cattle. 38 In accordance with the previous reports in Iran, 23,39 this study showed that the phylogroup B1 was dominant in calves. The phylogroup B2 had also the least frequency, both in calves and dairy cows, and these outcomes confirmed the previous investigations.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies revealed that phylogroup B1 was dominant among isolates from healthy cattle (Alizade et al, 2014). The analysis demonstrated that phylogroup B1 was more prevalent in isolates from diarrhoeic and septicemic calves in Iran (Ghanbarpour et al, 2009;Bihannic et al, 2014;Staji et al, 2015). It is interesting to note that subgroup B2 3 was found among isolates from both healthy and diarrhoeic calves, whereas subgroup A 0 was not found in all isolates.…”
Section: Discussionmentioning
confidence: 99%
“…All the fimbriae in Table 1 have been found associated with enterotoxin (genes) on clinical isolates of animals with diarrhea. However, F17 fimbriae are also expressed by diarrheagenic non-ETEC strains or by extra-intestinal E. coli (82), (83–85). Clinical isolates of ETEC have clonal properties, since there is a preferential association of fimbriae with certain enterotoxins and O-serotypes (Table 1) that have lead to their classification into major pathotypes (86).…”
Section: The Role Of Fimbriae In Etec Pathogenesismentioning
confidence: 99%
“…The crystal structures of the immunoglobulin-like lectin domains of two F17 adhesins (F17G and the related adhesin GafD) that bind N-acetylglucosamine were resolved (217, 218). Although an f17G gene encoding a different N-terminal sequence was recently described, it was not carried by an ETEC strain (85). …”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%